Analisis Indeks Ekologi Makroalga di Perairan Desa Juanga Kabupaten Pulau Morotai - Nurafni Nurafni; Djainudin Alwi; Samsir Baco (Jurnal Ilmiah Wahana Pendidikan, 2020)
The waters of Juanga Village have the potential for marine biological resources to vary considerably among seagrass coral reef ecosystems and various other types of biological resources. One of them is the macroalgae community. The aim of this study is to analyze the macroalgae ecological index in the waters of Juanga Village, Morotai Island Regency. The research began in November to December 2019. The data collection method used a quadrat transect of 1x1 m² in size. Ecological index data analysis includes Density (D), Type Composition (KJ), Diversity (H '), and Uniformity (E). The result showed highest composition of species at station I was Halimeda cunneata (24.49%), station II was Halimeda cunneata (33.333%), station III was of Halimeda cunneata and Padina australis (27.777%). The highest individual density at Station I of the Halimeda cunneata type (1,333 ind / m²), Station II of the Halimeda Cunneata type 1,056 (ind/m²), Station III of the Halimeda cunneata and Padina australis types has an individual density of 1,111 (Ind / m²). The diversity of macroalgae in the waters of Juanga Village is classified as "Low" with a value of H' 1,956 The results of the analysis of the Macalal Uniformity (E) Index in the waters of Juanga Village are classified as "High" because the average value obtained at the three research stations is 0.829.